Case Report: Concurrent two adenomatoid tumors of liver - Bi, Lei (Frontiers in Oncology, 2025)
A 40-year-old man with two accidentally discovered subcapsular liver tumors was admitted to our hospital for further treatment. Computed tomography (CT) and magnetic resonance imaging (MRI) revealed two hypervascular lesions, which showed marked enhancement in arterial phase and prolonged enhancement in portal venous phase. The patient had not received any prior treatment, and the two lesions were pathologically confirmed after partial hepatectomy. Hematoxylin-eosin staining revealed a partially cystic, highly vascular, and well-encapsulated neoplasm. Immunohistochemistry findings demonstrated that the epithelioid tumor cells were positive for vimentin, calretinin, WT-1, cytokeratin, CD 31, CD 34, and D2-40, which supported their mesothelial origin. Immunohistochemistry for a mesothelial marker should be performed for determining the presence of an adenomatoid tumor when benign epithelioid cells are seen.